Impact of neoadjuvant chemotherapy on postoperative morbidity after gastrectomy for gastric cancer - Téoule, Patrick (Digestive surgery, 2015)
Background/Aims: Patients with locally advanced gastric cancer benefit from neoadjuvant chemotherapy. Potential disadvantages of neoadjuvant chemotherapy include increased surgical complications, leading to increased postoperative morbidity. Methods: We retrospectively studied medical records of 135 patients with resectable cancer of the stomach who underwent gastrectomy between 2002 and 2009. The impact of neoadjuvant chemotherapy on postoperative morbidity was investigated. We compared demographic, clinical and operative data, morbidity and mortality from 105 patients who received surgical treatment immediately after diagnosis (SURG group), versus 30 patients who first received neoadjuvant chemotherapy (CHEMO group). Results: Demographic, clinical and surgical procedure parameters did not differ significantly between both groups. Postoperative morbidity was 46.7% in CHEMO- and 41.9% in SURG-patients (p = 0.680). There were eight cases of death, 2/30 (6.7%) in CHEMO and 6/105 (5.7%) in the SURG group (p = 1). The overall complications according to Clavien-classification did not differ significantly (p = 0.455). The wound infection rate (23.3 vs. 3.8%; p = 0.002) and insufficiency of the duodenal stump (13.3 vs. 1.9%; p = 0.022) were significantly higher in the CHEMO group. Conclusion: This study showed no significant impact of neoadjuvant chemotherapy on postoperative morbidity after gastrectomy using the Clavien-classification. Only an increase in wound infections in CHEMO compared with the SURG group were noted. Therefore, neoadjuvant chemotherapy can be considered safe and feasible.